Challenging challenges: a metaphysical redress of van den Haag's retributive axiom – unequal justice over equal injustice - Traub, Craig Michael (Institute of Criminology, 2026)
For over thirty years Ernest van den Haag repeatedly asserted a controversial claim in favour of the death penalty. He argued that, regardless of the extent to which capital punishment sentences are unequally, arbitrarily, or even racially, maldistributed among offenders, capital punishment is always a morally valid sentence in se. His controversial claim is rooted in the theory of retributive justice, as he appeals to the offender's individual moral desert to justify capital punishment for the crime of (first-degree) murder. Thus, van den Haag summarised his claim into a logical axiom - that unequal justice (i.e. capital punishment) is always preferable to equal injustice (i.e. abolitionism or life imprisonment). Van den Haag challenged abolitionists to refute his axiom by using his same retributive foundation. This is something abolitionists have been unable to do without resorting to consequentialist or hybrid reasoning. This theoretical dissertation has sought to find the flaws in van den Haag's logic and dispute his axiom on his own retributive grounds utilising, particularly, racial maldistribution of capital sentences. In this dissertation four attempts are made to dispute his axiom and the following arguments are identified: (i) an internal inconsistency within van den Haag's axiom; (ii) an argument for an implicit illegitimate authority, as well as (iii) an argument for an explicit illegitimate authority; and finally, (iv) an argument concerning the subjective experience of the offender when presented with a sentence of death. It is, however, the final argument that carries the most weight in disputing van den Haag's axiom. Thus, this dissertation has met his challenge by rendering the death penalty immoral in itself, even when the justification for the death penalty is retributive.